Development of Semester Final Examination (UAS) Test Instruments Based on Higher Order Thinking Skills (HOTS) in the IPAS Subject for Fourth Grade Elementary School - Nisrayanti Nisrayanti; Baso Intang Sappaile; Mansyur Mansyur (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This research aims to develop a Semester Final Examination (UAS) test instrument based on Higher Order Thinking Skills (HOTS) for the IPAS subject in the 4th grade of Elementary School. The background of this research is the still low ability of students' higher-order thinking, caused by the dominance of Lower Order Thinking Skills (LOTS) based questions in learning evaluation. Therefore, it is necessary to develop an assessment instrument that can measure students' critical thinking, analytical, and problem-solving abilities. This research uses the Research and Development (R&D) method with a development model that includes the stages of needs analysis, design, product development, expert validation, testing, and product revision. Validation was conducted by 2 validators consisting of subject matter experts and evaluation experts, while the instrument trial was carried out on 30 fourth-grade elementary school students. The validation results showed that the instrument received a very valid category with a feasibility percentage of 89%, while the reliability results indicated a reliability coefficient of 0.87 with a high category. The developed instrument consists of HOTS-based UAS questions on the IPAS material for fourth-grade elementary school students and is deemed suitable for use after undergoing the validation and revision process. This instrument is also deemed capable of measuring students' higher-order thinking skills more effectively compared to conventional instruments. The main contribution of this research is to produce a valid, reliable, and practical HOTS-based evaluation instrument to improve the quality of IPAS learning assessments in elementary schools.